Loci associated with spontaneous abortion in primiparous Holstein cattle - Suarez, Emaly M.; Kelson, Victoria C.; Kiser, Jennifer N.; Davenport, Kimberly M.; Murdoch, Brenda M.; Herrick, Allison L.; Neibergs, Holly L. (Frontiers in Veterinary Science, 2025)
IntroductionSpontaneous abortion (SA) in cattle refers to pregnancy loss occurring between days 42 and 260 of gestation. SA is costly, inefficient, and often leads to premature culling of cows.MethodsThis study aimed to identify loci associated with SA in primiparous Holstein cows by conducting a genome-wide association analysis of cows bred via artificial insemination (AI; 679 controls and 69 cases that aborted) or that were embryo transfer (ET) recipients (236 controls and 41 cases) from a single dairy.ResultsIn AI-bred cows, 86 loci (413 single nucleotide polymorphisms or SNPs) and 168 positional candidate genes were associated (FDR <0.05) with SA, while in ET recipients, 4 loci (10 SNPs) and 16 positional candidate genes were associated (FDR <0.05) with SA. No SA-associated loci were shared between AI-bred or ET recipient cows, but nine associated loci (FDR <0.05) in AI-bred cows were shared with AI-bred heifers.DiscussionThe difference in loci associated with AI-bred and ET recipient cattle may be due to differences in mechanisms associated with the maintenance of pregnancy between in vivo and in vitro derived embryos, or a larger sample size may be needed to identify additional shared loci. Identifying loci associated with SA in AI-bred and ET recipient cows provides an opportunity to enhance selection for reproductive efficiency in Holstein cattle.